A comparative study of the vocabulary in primary school Chinese textbooks in the perspective of distribution, usage & level of difficulty - Quek, Germaine Jiamin (Nanyang Technological University, 2021)
There were various previous researches on analysing Chinese textbooks, however few did comparative study on the different syllabuses. Dr Luo Qingming, in 2008, published a comparative study on three sets of Chinese textbooks, focusing on the evolution, characteristics and shortcomings of the textbooks. Concrete suggestions were also put forward for future planning of syllabuses. This comparative study, that is both diachronic and synchronic, of all 4 sets of textbooks would be a first. [1st Award]